The Role of Women in the Preservation of the Acehnese Language: Ecolinguistics and Gender Perspectives - Ristawati, Ristawati; Rahayu, Ririn; Iqbal, Muhammad; Muntazar, Muntazar (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2025)
This study aims to analyse the role of women in the preservation of the Acehnese language with an ecolinguistics and gender approach. The background of this research is the threat to the continuity of the Acehnese language which is marginalized by the dominance of the Indonesian language, both in the education and media sectors. Acehnese women, as the main agents in the transmission of language to the younger generation, play an important role in maintaining the sustainability of the Acehnese language in the domestic and community spheres. This research uses a qualitative approach with a case study method, which involves in-depth interviews with Acehnese women in various community groups, as well as observations on the use of the Acehnese language in daily life. The data analysis technique was carried out with a thematic analysis approach to identify the role of women, the challenges faced, and the conservation strategies applied. The results show that although Acehnese women play a central role in the preservation of the Acehnese language, their role is often not institutionally recognized. Also, social and economic pressures that encourage the switch to Indonesian are obstacles in the preservation of the language. This research suggests the need for more inclusive policies that actively involve women in the revitalization of the Acehnese language, as well as structural support that can strengthen their role in the preservation of the language. Abstrak Penelitian ini bertujuan untuk menganalisis peran perempuan dalam pelestarian bahasa Aceh dengan pendekatan ekolinguistik dan gender. Latar belakang penelitian ini adalah adanya ancaman terhadap kelangsungan bahasa Aceh yang terpinggirkan oleh dominasi bahasa Indonesia, baik dalam sektor pendidikan maupun media. Perempuan Aceh, sebagai agen utama dalam transmisi bahasa kepada generasi muda, memainkan peran penting dalam menjaga keberlanjutan bahasa Aceh di ranah domestik dan komunitas. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, yang melibatkan wawancara mendalam dengan perempuan Aceh di berbagai kelompok masyarakat, serta observasi terhadap penggunaan bahasa Aceh dalam kehidupan sehari-hari. Teknik analisis data dilakukan dengan pendekatan analisis tematik untuk mengidentifikasi peran perempuan, tantangan yang dihadapi, serta strategi pelestarian yang diterapkan. Hasil penelitian menunjukkan bahwa meskipun perempuan Aceh memainkan peran sentral dalam pelestarian bahasa Aceh, peran mereka sering kali tidak diakui secara institusional. Selain itu, tekanan sosial dan ekonomi yang mendorong peralihan ke bahasa Indonesia menjadi kendala dalam pelestarian bahasa Aceh. Penelitian ini menyarankan perlunya kebijakan yang lebih inklusif yang melibatkan perempuan secara aktif dalam revitalisasi bahasa Aceh, serta dukungan struktural yang dapat memperkuat peran mereka dalam pelestarian bahasa tersebut.